Link Slab Capacity In Bridges Supported By Lead Rubber Bearing And Elastomer - Novikasari, Inas; Rosyidah, Anis (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2019)
Debris accumulation in bridge slab gaps which use expansion joints can restrain deck expansion, causing undesirable forces on floor deck and damage to the structure. In order to avoid the worst possibility that can occur, an alternative using link slab is utilized. The use of link slab at high level seismic force location, requires the Seismic Isolation System on bridge to reduce the seismic force. The application of Seismic Isolation System can be conducted by Lead Rubber Bearing (LRB) type of seismic isolator. This study compares the use of Lead Rubber Bearing (LRB) and elastomer on bridge link slabs against the dimension of the link slab. In this study structural modeling used 2 models: bridges supported by elastomer and bridges supported by LRB with software-made. The link slab analysis approach used were analytical methods or classical methods. Based on results of the analysis, the width of the crack that occured on bridge supported by LRB is 0.218 mm while on the bridge supported by elastomer is 0.269 mm. The use of Lead Rubber Bearing (LRB) type of support will give more advantages to the design of the link slab since it results in smaller crack design criteria.